PENGARUH ISLAMIC BRANDING, HALAL AWARENESS, DAN ISLAMIC LIFESTYLE TERHADAP KEPUTUSAN PEMBELIAN DENGAN RELIGIUSITAS SEBAGAI VARIABEL MODERATING (STUDI KASUS PADA KONSUMEN WARDAH DI JAWA BARAT) - Putri, Nurul Hikmah Rizki; Pertiwi, Imanda Frimantyas Putri (Jurnal Ilmiah Wahana Pendidikan, 2024)
The halal industry is presently a substantial enterprise, gaining popularity both within the country and internationally. Wardah emerged as a pioneer of halal brand cosmetics, making it easier for users to consume halal products. This study aims to ascertain the effect of Islamic branding, halal awareness, and Islamic lifestyle on purchase decisions, with religiosity as a moderating variable of Wardah customers in West Java. The required respondents for this study were 100 individuals selected using the purposive sampling technique with the Lameshow formula. The results showed that Islamic branding had a negative and nonsignificant impact on purchase decisions. Halal awareness had a positive and nonsignificant impact on purchase decisions, while Islamic lifestyle had a positive and nonsignificant impact. Religiosity had a negative and nonsignificant impact on purchase decisions. Additionally, religiosity did not moderate the relationship between halal awareness and purchase decisions. Religiosity also did not moderate the relationship between Islamic lifestyle and purchase decisions. However, religiosity moderated the relationship between Islamic branding and purchase decisions.